Monitoring data encryption method for howitzer shell transfer arm using chaos and compressive sensing. (September 2019) - Liu, Xi; Hou, Baolin; Zhao, Qiangqiang
A novel data encryption method is presented for howitzer shell transfer arm using chaos and compressive sensing. Data are stored in the embedded fault diagnosis machine using chaos and compressive sensing, so the encrypted data are more secure in the embedded system and in the process of transmission with host computer. When the host computer extracts the operation data of the howitzer shell transfer arm monitored by the fault diagnosis machine, firstly, the encrypted data in the embedded diagnostic machine are read, then decrypted, and then the original signal is reconstructed by the orthogonal matching pursuit algorithm for further analysis and processing. The similarity degree between the reconstructed data and the original data is 0.947, the key space of the algorithm is( 2 64 ) 2 0 48 ∗ 2 00 ∗ ( 2 64 ) N, and the algorithm is sensitive to the key. The result shows that the method can effectively save a large number of confidential data.